Pharmacological Profiling of Substituted Benzothiazoles: Insights into Structure-Activity Relationships (Journal of Advances and Scholarly Researches in Allied Education, 2024)
A series of novel 1,3,4-oxadiazole derivatives incorporating benzothiazole moieties were synthesized and characterized for their structural and spectroscopic properties. The compounds, designated as 6a–6f, were prepared by coupling benzothiazole derivatives with various substituted phenyl groups through thiomethyl linkages on the oxadiazole ring. Structural confirmation was achieved using FTIR, 1H and 13C NMR spectroscopy, and mass spectrometry. The synthesized compounds exhibited distinct spectral characteristics, including aromatic C–H stretching (3045–3061 cm⁻¹), C=N stretching (1615–1619 cm⁻¹), and functional group-specific absorptions such as nitro (1548 cm⁻¹) and methoxy (–OCH₃) stretches (1246–1038 cm⁻¹). Elemental analyses showed good agreement between calculated and observed values, confirming the molecular compositions. The synthesized compounds present potential applications in pharmaceutical and materials science domains, with their unique structural framework offering scope for further exploration in biological and electronic applications. This study underscores the efficacy of the synthetic route and provides insights into the physicochemical attributes of benzothiazole-based oxadiazoles.